The Effect of Capital Structure and Profitability on Company Value in Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period - Leonardo Gianfranco Jeharut; Elly Lestari; Fitria Setyaningrum (International Journal of Management and Business, 2026)
This study aims to determine the influence of capital structure and profitability on the value of companies in the property and real estate sectors listed on the Indonesia Stock Exchange for the 2019–2023 period. A sample of 17 companies was selected using the purposive sampling method. Data analysis was carried out by multiple linear regression using SPSS version 21. The study results show that first, capital structure has a partial significant effect on company value, which means that effective management of capital structure can increase company value. Second, profitability also has a partial positive effect, where increased profitability will increase the company's value, reflecting good financial performance and the ability to generate future cash flow. Third, simultaneously, capital structure and profitability significantly influence the company's value, emphasizing that the combination of good capital structure management and increased profitability is a key strategy to maximize the company's value.